2007
DOI: 10.1016/j.abb.2007.09.018
|View full text |Cite
|
Sign up to set email alerts
|

12(S)-Hydroperoxyeicosatetraenoic acid (12-HETE) increases mitochondrial nitric oxide by increasing intramitochondrial calcium

Abstract: 12(S)-hydroxyeicosatetraenoic acid (12-HETE) is one of the metabolites of arachidonic acid involved in pathological conditions associated with mitochondria and oxidative stress. The present study tested effects of 12-HETE on mitochondrial functions. In isolated rat heart mitochondria, 12-HETE increases intramitochondrial ionized calcium concentration that stimulates mitochondrial nitric oxide (NO) synthase (mtNOS) activity. mtNOS-derived NO causes mitochondrial dysfunctions by decreasing mitochondrial respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
35
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 36 publications
5
35
1
Order By: Relevance
“…12-HETE, 20-HETE, and 8-HDoHE), but not 14,15-EET, 9-oxoODE, or PGE 2 , sensitize mitochondria to the calcium-induced loss of membrane potential. These findings are supported by previous studies that showed arachidonic acid-and 12-HETE-facilitated Ca 2ϩ overload resulting in abnormal oxidative stress and mitochondrial dysfunction (44,49). Therefore, the results of this study suggest that iPLA 2 ␥ facilitates production of oxidized lipid metabolites by providing PUFAs and/or polyunsaturated fatty acyl lysolipids, which can be further hydrolyzed to non-esterified PUFAs by lysophospholipases and subsequent oxidation by downstream oxygenases.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…12-HETE, 20-HETE, and 8-HDoHE), but not 14,15-EET, 9-oxoODE, or PGE 2 , sensitize mitochondria to the calcium-induced loss of membrane potential. These findings are supported by previous studies that showed arachidonic acid-and 12-HETE-facilitated Ca 2ϩ overload resulting in abnormal oxidative stress and mitochondrial dysfunction (44,49). Therefore, the results of this study suggest that iPLA 2 ␥ facilitates production of oxidized lipid metabolites by providing PUFAs and/or polyunsaturated fatty acyl lysolipids, which can be further hydrolyzed to non-esterified PUFAs by lysophospholipases and subsequent oxidation by downstream oxygenases.…”
Section: Discussionsupporting
confidence: 79%
“…mitophagy). This study demonstrates the unanticipated and dramatic accumulation of oxidized fatty acids, including large amounts of oxidized linoleic acid metabolites, which likely originate from cardiolipin, the major pool of esterified linoleic acid in the mitochondrial compartment as well as a plethora of eicosanoid metabolites known to have adverse effects on cardiac myocyte membrane proteins, inflammation, and bioenergetics (43)(44)(45). The benefits of iPLA 2 ␥ loss of function investigated in this study include the attenuation of many of the molecular mechanisms known to predispose to myocardial tissue damage during pathological processes, including cardiac ischemia/reperfusion (46).…”
Section: Discussionmentioning
confidence: 99%
“…For example, lipoxygenase inhibi- tion has been demonstrated to block insulin-mediated glucose uptake in cultured ventricular myocytes suggesting the importance of downstream lipoxygenase metabolites in insulin signaling (61). Furthermore, 12-HETE has been previously demonstrated to increase myocardial mitochondrial Ca 2ϩ content as well as mitochondrial nitric-oxide synthase activity, which led to increased apoptosis in HL-1 cardiac myocytes (51,62). Intriguingly, arachidonic acid has been implicated in MPT pore opening in several tissues, and inhibition of the release of AA from mitochondria prevented pore opening (42,63).…”
Section: Discussionmentioning
confidence: 99%
“…Further mechanisms of 12-HETE action include stimulating oxidative stress by increasing intramitochondrial ionized calcium concentrations in cardiac myocyte mitochondria and stimulating mitochondrial nitric oxide synthase activity, which goes on to induce cell apoptosis (16). A study of beta cells in the pancreases of diabetic patients showed that inflammatory cytokines can induce 12-lipoxygenase RNA and protein expression and that an increase in 12-HETE levels inhibits insulin secretion, reduces beta cell metabolic activity, and induces cell death in islet cells (17,18).…”
Section: Discussionmentioning
confidence: 99%